Comparison of assessment tools in acute upper gastrointestinal bleeding: which one for which decision. (2nd January 2022) - Marmo, Riccardo; Soncini, Marco; Bucci, Cristina; Zullo, Angelo
Abstract: Background: Upper GI bleeding (UGIB) remains a common emergency with significant mortality. Scores help triage patients, but it is still unclear which score should be used in the different decision-making moments to identify patients at high or low death risk. We aimed to compare the overall performances of the most validated scores and their cut-off performance to identify patients at low and high death risk. The secondary outcome was to compare the scores' performance for predicting therapeutic endoscopy, the need for transfusion(s), rebleeding, and surgery/interventional radiology. Methods: We conducted a prospective multicenter cohort study, including consecutive UGIB patients admitted to 50 Italian hospitals. We collected information to calculate the Rockall, the Progetto Nazionale Endoscopia Digestiva (PNED), the AIMS65, the Glasgow-Blatchford (GBS), and the Age, Blood tests, Comorbidities (ABC) scores, together with demographic figures, clinical data, and outcomes. Results: We obtained complete data of 2307 outpatients, including 1887 non-variceal and 420 variceal bleeders. Our cohort's mean age was 67.5 years, with a prevalence of male gender (69%). The GBS has the best overall performance (ROC 0.74) compared to the other scores in identifying low-risk patients ( p  < .001). At the cut-off 0–1, both GBS and ABC scores provide the highest PPV (100%) for low-risk patients. ABC and PNED scores are the most useful ones (for AUC >80) to assess the high-risk patients for mortality. Conclusions: At admission, GBS and ABC scores identify low-risk patients suitable for outpatient management, while PNED and ABC scores identify high-risk patients. During hospitalization, the PNED score should be used to re-assess the mortality risk if a modification of clinical status occurs.